2004
DOI: 10.1021/ja044889l
|View full text |Cite
|
Sign up to set email alerts
|

Bromoporphyrins as Versatile Synthons for Modular Construction of Chiral Porphyrins:  Cobalt-Catalyzed Highly Enantioselective and Diastereoselective Cyclopropanation

Abstract: 5,10-Bis(2',6'-dibromophenyl)porphyrins bearing various substituents at the 10 and 20 positions were demonstrated to be versatile synthons for modular construction of chiral porphyrins via palladium-catalyzed amidation reactions with chiral amides. The quadruple carbon-nitrogen bond formation reactions were accomplished in high yields with different chiral amide building blocks under mild conditions, forming a family of D2-symmetric chiral porphyrins. Cobalt(II) complexes of these chiral porphyrins were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(112 citation statements)
references
References 17 publications
2
108
0
2
Order By: Relevance
“…A particularly interesting set of reactions proceeds through metal-carbenoid intermediates that had never been exploited for catalysis by heme proteins. The synthetic porphyrin systems relied on synthetic activated reagents such as ethyldiazoacetate (EDA) to generate the metal carbenoid, which could then react with olefins or insert the carbene into various N-H, C-H, or O-H bonds (Baumann et al 2007;Chen et al 2004;Wolf et al 1995). That the metal-carbenoid intermediate resembles compound I in the native P450 catalytic cycle (Fig.…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
“…A particularly interesting set of reactions proceeds through metal-carbenoid intermediates that had never been exploited for catalysis by heme proteins. The synthetic porphyrin systems relied on synthetic activated reagents such as ethyldiazoacetate (EDA) to generate the metal carbenoid, which could then react with olefins or insert the carbene into various N-H, C-H, or O-H bonds (Baumann et al 2007;Chen et al 2004;Wolf et al 1995). That the metal-carbenoid intermediate resembles compound I in the native P450 catalytic cycle (Fig.…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
“…Hence, substrate redox non-innocence is not just a chemical curiosity, and the cyclopropanation reactions mediated by cobalt porphyrins provided prime examples of catalytic reactions proceeding via carbene radicals behaving as (Fig. 4) [36][37][38] led to unprecedented reactivity and selectivity, which was explained by the increased nucleophilic character of the carbene radical compared to an unreduced Fischer-type carbene, allowing the pursuit of more challenging substrates such as electrondeficient olefins. The cooperation between the carbene radical and the metal is of crucial importance for catalysis and is actually similar to the way metallo-enzymes gain control over radicals in several enzymatic processes.…”
Section: Carbon-centered Radicals In Catalysismentioning
confidence: 99%
“…On the other hand, a trans selectivity was observed by running cyclopropanations in the presence of porphyrin complexes reported in Scheme 8, but unfortunately enantioselectivities were not satisfying. Since then, Zhang et al developed the synthetic procedure [75,76] shown in Scheme 9, by using bromoporphyrins as synthons, to reach a wide pool of chiral porphyrins with D 2 symmetry ( Figure 6). …”
Section: Cobalt-catalysed Reactionsmentioning
confidence: 99%